Anthropogenic Effects on Metal Content in Urban Soil From Different Parent Materials and Geographical Locations: A Vancouver, British Columbia, Canada, Study. Issue 4 (April 2015) - Thomas, E.C.; Lavkulich, Les M.
Abstract : Abstract: Growing safe food crops in urban settings requires soil condition assessment because many sites may be metal contaminated. Of particular concern are trace metals found at urban sites as a result of litter, construction materials, industrial development, and traffic patterns. Although all soils contain trace metals inherited from the parent material, anthropogenic influences can influence and increase metals' plant availability. Different urban activities located on soils derived from three parent materials, marine, glacial marine, and glacial till, were selected in Metro Vancouver to assess trace metal concentrations in the urban soils. Estimates of total ( aqua regia ) and available (dilute HCl) trace metals (Cu, Mn, Ni and Pb ) were compared among the sites and between the surface soil and the underlying parent material to assess potential environmental risks associated with location of the urban sites. Comparisons were made to metal concentration standards in published government guidelines. Although urban activities do affect metal amounts, parent materials must be considered when assessing anthropogenic effects of trace metals in soils because metal contents vary among different parent materials. Results indicate that surface soil metal concentrations are influenced by geographical location within the urban setting and soil management practices. For a rapid and reproducible determination of potential trace metal concentrations, the use of 0.1 M HCl provides a useful initial assessment.